Book Review: Capital as Power - Owen Lynch (The Bichler and Nitzan Archives, 2021)
FROM THE REVIEW: You see, I'm trying to give you a picture of what it is like to read this book, and the experience of having a tantalizing insight dangled in front of you but then being forced to read far more history and statistics than you would really like to understand it is essentially all of Capital as Power. Capital as Power is long, but extremely full of content [...] Bichler and Nitzan write in a very engaging way; not necessarily easy to read but certainly action-packed. And there are many, many interesting historical nuggets in the book, like the history of GM's EV1 car. [U]nlike the laws of economics which mostly claim to be universal across time, the strength of Capital as Power is that they can identify what things are true about some periods, and not of others, and integrate these assumptions into their models. In other words, rather than being a general theory of economics, Capital as Power is a general theory of the space of possible capitalist politics, or as Bichler and Nitzan seem to be so happy to coin, a general theory of possible capitalist creorders.
Keywords: P16; P1; 330; capital as power